Comparative efficacy of fungicides for in vitro control of sheath rot pathogen associated with grain discoloration of rice / Muhammad Alimie Dol Bahar - Dol Bahar, Muhammad Alimie (Faculty of Plantation and Agrotechnology, 2019)
Rice is one of the important crop in the world that influence in many aspects such as economic, social lifestyle and food consuming by human. The previous economic studies show that more than 90% of rice were produce of by human and being consumed most of the people in the world. Sheath rot disease has become major disease in the rice that is difficult to eradicate and need a proper technique to eliminate this disease. Therefore, the main objective of this study is identified the most effective fungicide to control Sarocladium oryzae that caused sheath rot disease. Next, to construct the rank of effectiveness between different active ingredients of fungicides against sheath rot disease. Following with the last objective is to determine the most economical active ingredient to use to control the disease. In this study, four different active ingredients Azoxystrobin, Propiconazole and Tricyclazole, Difenoconazole and Propiconazole and Carbendazim was chosen based on previous studies that have been conducted to determine its antifungal activity against sheath rot disease in vitro. Sarocladium oryzae was placed on the PDA amended with different of fungicides. The less mycelia growth diameters for antifungal activity proven the effectiveness of active ingredient against Sarocladium oryzae using food poisoning technique in vitro studies. For in vivo studies, the healthy rice was inoculated by sheath rot disease caused by Sarocladium oryzae for pathogenicity test. The data obtained in vitro studies was analyses using ANOVA in SPSS software. The result showed that active ingredient Propiconazole and Tricyclazole, Difenoconazole and Propiconazole and Carbendazim have the highest efficacy rate in terms of reducing the mycelia growth compared Azoxystrobin tested in this study.